Adverse Drug Reactions Reporting By Consumers In The State Of Penang, Malaysia : Perspectives From Healthcare Professionals And Consumers - Alshakaa, Muhammed Ahmed Mahdi (2013)
It is essential to monitor adverse drug reactions (ADRs) in order to minimize or prevent harm to patients arising from their medicines. The study first compares the drug systems used in Malaysia, Australia and Sweden, and assessing several sustantial aspects among the professional in healthcare against ADR and pharmacovigilance. A comparative analysis that make use of Leavitt's Diamond Model has been adapted by Scott in terms of several components. The structure process and the outcome of drugs safety system in all three countries become the variables and outcome measure in this research.